The Effect of Skin Type And Cleansing Frequency On Acne Incidence In Medical Students - Dea Putri Ramadhani; Dian Amelia Abdi; Andi Alamanda Irwan; Nurelly Noro Waspodo; Andi Sitti Fahirah Arsal (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2026)
Acne vulgaris is a common dermatological problem experienced by adolescents and young adults, with a high prevalence among university students. This study aims to analyze the effects of skin type and facial-cleansing frequency on the incidence of acne vulgaris among students at the Faculty of Medicine, Universitas Muslim Indonesia. This quantitative analytical study with a cross-sectional approach involved 109 respondents selected using purposive sampling. The results showed that oily skin was the most susceptible to acne vulgaris, with twice-daily facial cleansing being the most optimal frequency for reducing acne incidence. Too frequent or too infrequent facial cleansing can worsen acne. In addition, a significant relationship was found between skin type and facial cleansing frequency in influencing the severity of acne vulgaris. This study suggests that students, especially those with oily skin, maintain facial hygiene with an optimal frequency of twice a day and choose cleansing products that are suitable for their skin type. Medical faculties are expected to provide education on skin care and risk factors for acne vulgaris. Further research is recommended to include additional variables such as cosmetic use, diet, stress, and sleep quality, as well as using a longitudinal approach to gain further understanding of changes in acne severity.